Front Cover: Harnessing the Maltodextrin Transport Mechanism for Targeted Bacterial Imaging: Structural Requirements for Improved in vivo Stability in Tracer Design (ChemMedChem 3/2018). (8th February 2018) - Axer, Alexander; Hermann, Sven; Kehr, Gerald; Clases, David; Karst, Uwe; Fischer‐Riepe, Lena; Roth, Johannes; Fobker, Manfred; Schäfers, Michael; Gilmour, Ryan; Faust, Andreas
Abstract : The Front Cover shows a blueprint of a defined carbohydrate (candy) that is literally devoured by the bacterial cell via maltodextrin transporters. Attaching an imaging label to this carbohydrate allows it to be tracked (yellow shine) and potentially allows sensitive detection and localization of bacterial infection in vivo. The study has identified essential structural features of the tracer molecule to make it less vulnerable to enzymatic degradation (green icons) in the blood. This approach facilitates intracellular accumulation via maltodextrin transporters thereby lightening up the bacterial cell and colony, respectively. More information can be found in the Full Paper by Ryan Gilmour, Andreas Faust et al. onpage 241 in Issue 3, 2018 (DOI:10.1002/cmdc.201700543 ).